Head‐turning morphologies: Evolution of shape diversity in the mammalian atlas–axis complex. (19th August 2019) - Vander Linden, Abby; Campbell, Kristin M.; Bryar, Erin K.; Santana, Sharlene E.
Abstract: Mammals flex, extend, and rotate their spines as they perform behaviors critical for survival, such as foraging, consuming prey, locomoting, and interacting with conspecifics or predators. The atlas–axis complex is a mammalian innovation that allows precise head movements during these behaviors. Although morphological variation in other vertebral regions has been linked to ecological differences in mammals, less is known about morphological specialization in the cervical vertebrae, which are developmentally constrained in number but highly variable in size and shape. Here, we present the first phylogenetic comparative study of the atlas–axis complex across mammals. We used spherical harmonics to quantify 3D shape variation of the atlas and axis across a diverse sample of species, and performed phylogenetic analyses to investigate if vertebral shape is associated with body size, locomotion, and diet. We found that differences in atlas and axis shape are partly explained by phylogeny, and that mammalian subclades differ in morphological disparity. Atlas and axis shape diversity is associated with differences in body size and locomotion; large terrestrial mammals have craniocaudally elongated vertebrae, whereas smaller mammals and aquatic mammals have more compressed vertebrae. These results provide a foundation for investigating functional hypotheses underlying the evolution of neck morphologies across mammals.